Education Based on Local Wisdom - Chaer, Moh Toriqul; Rochmah, Elfi Yuliani; Sukatin, Sukatin (Journal of Islamic Education, 2021)
This article aims to examine the power of local wisdom in education. Local knowledge will only last if local learning is applied concretely in everyday life. Efforts to represent the concept of education are not merely normative; only stated and explained, but attempted performative form. For example, local wisdom in education policies by the State is implementing character education policies based on local knowledge, culture, and culture. This research is library research by making library materials the primary data source. The research data were obtained from several pieces of literature related to the general description of education in Indonesia, educational problems and character education strategies. The research data were analysed using descriptive-analytical techniques with an inductive mindset. Implementing efforts to conserve various elements of local wisdom, traditions and local institutions, including norms, customs and culture, can function effectively in education. The goals of education are based on local strengths and characteristics that can advocate for disparities and social-cultural discrimination in society and contribute to better cultural education.